PEMETAAN GEOGRAPHIC INFORMATION SYSTEM (GIS) KERUSAKAN POHON PADA BERBAGAI FUNGSI HUTAN DI PROVINSI LAMPUNG - Prayogi Saiful Anwar; Rahmat Safe’i; Arief Darmawan; Hari Kaskoyo (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2021)
Sustainable forest management can be achieved through an assessment of forest health. The tree damage assessment aims to measure the level of disturbance in the trees so that in the end forest conditions can be detected and decision making by forest managers can be carried out appropriately. This study aims to assess tree damage in several forest functions. The use of the Geographic Information System (GIS) is vital, where the distribution of tree damage conditions can be spatially determined, so that it can be described properly. The results of the analysis showed 17 conservation forests for healthy trees, 30 medium trees and 105 damaged trees. 51 production forests for healthy trees, 82 medium trees and 128 damaged trees. There are 75 medium trees and 56 damaged trees. The health condition of trees in several forest functions is in a damaged condition and needs attention from forest managers. There needs to be action by the manager in the form of maintenance such as pruning, silencing and fertilizing as well as harvesting actions with the right timing.